2021
DOI: 10.1097/j.pain.0000000000002471
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury in mice affects central and peripheral pathology in a severity-dependent manner

Abstract: Chronic pain is a common medical complication experienced by those living with spinal cord injury (SCI) and leads to worsened quality of life. The pathophysiology of SCI pain is poorly understood, hampering the development of safe and efficacious therapeutics. We therefore sought to develop a clinically relevant model of SCI with a strong pain phenotype and characterize the central and peripheral pathology after injury. A contusion (50 kdyn) injury, with and without sustained compression (60 seconds) of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 146 publications
(199 reference statements)
0
2
0
Order By: Relevance
“…Pathologically, the blood-spinal-cord barrier (BSCB) is disruptured after spinal cord injury 49 , 50 , and leads to the infiltration of peripheral inflammatory cells and factors into the lesion area 51 . Recent studies have shown that peripheral macrophages affect the microenvironment of lesion area after SCI 52 - 54 , and crosstalk between peripheral macrophages and vessels endothelial cells in the lesion area after SCI is a potential therapy for SCI 55 . Moreover, ependymal cells can behave as multipotent spinal cord stem cells and form new neurons and glial cells 56 - 59 , which may affect the microenvironment of lesion area after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, the blood-spinal-cord barrier (BSCB) is disruptured after spinal cord injury 49 , 50 , and leads to the infiltration of peripheral inflammatory cells and factors into the lesion area 51 . Recent studies have shown that peripheral macrophages affect the microenvironment of lesion area after SCI 52 - 54 , and crosstalk between peripheral macrophages and vessels endothelial cells in the lesion area after SCI is a potential therapy for SCI 55 . Moreover, ependymal cells can behave as multipotent spinal cord stem cells and form new neurons and glial cells 56 - 59 , which may affect the microenvironment of lesion area after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factors and Toll-like receptors were the key research factors ( Zeraati et al, 2019 ; Haghighat et al, 2021 ). Pathological experiments were the primary study methodology, while probiotic therapy was the primary research topic ( Akbari et al, 2016 ; Kozyrev et al, 2020 ; Bannerman et al, 2022 ; Pochakom et al, 2022 ). Notably, including “schizophrenia” (burst strength 4.35), “pathology” (burst strength 3.81), and “psychiatric disorder” (burst strength 3.26), which are the current research frontiers in this field and are currently within the burst period.…”
Section: Discussionmentioning
confidence: 99%